2016
DOI: 10.1039/c5an02140e
|View full text |Cite
|
Sign up to set email alerts
|

A new insight into the interaction of cisplatin with DNA: ROA spectroscopic studies on the therapeutic effect of the drug

Abstract: Raman optical activity (ROA) spectroscopy has been applied for the first time to study the interaction of cisplatin with DNA. The knowledge about the structure of DNA-metal ion cross-links and hence the mechanism of the drug action is fundamental for the development of new antitumor drugs. At the same time, there is an urgent need to search for new methods for monitoring of this effect at the therapeutic dose of a drug. We have demonstrated that ROA spectroscopy is a sensitive technique with the capability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…These studies provide valuable information about the intermolecular interactions 8 , base pairing 9 , and tautomerization 10 of nucleobases. IR and Raman spectroscopy have been used extensively in the investigations of the structure, interactions and properties of nucleobases and related compounds 11–13 . In contrast, investigations of near-infrared (near-IR; NIR) spectra of nucleobases are very rare 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies provide valuable information about the intermolecular interactions 8 , base pairing 9 , and tautomerization 10 of nucleobases. IR and Raman spectroscopy have been used extensively in the investigations of the structure, interactions and properties of nucleobases and related compounds 11–13 . In contrast, investigations of near-infrared (near-IR; NIR) spectra of nucleobases are very rare 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin (cis-diaminedichloro-platinum, CDDP) is one of the most active chemotherapeutic agents used for the treatment of a large variety of malignancies, especially testicular and ovarian carcinomas, even if its clinical utility is restricted by both toxicological and tumor resistance drawbacks [ 1 , 2 ]. CDDP activity and toxicity is mainly due to DNA binding [ 3 , 4 ], occurring via both inter- and intrastrand crosslinks, that suppresses DNA replication and also RNA transcription. Specifically, CDDP interacts with the DNA nucleobases forming stable platinum–nitrogen covalent bonds, which lead to irreversible adducts responsible for cisplatin antitumor activity [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…CDDP activity and toxicity is mainly due to DNA binding [ 3 , 4 ], occurring via both inter- and intrastrand crosslinks, that suppresses DNA replication and also RNA transcription. Specifically, CDDP interacts with the DNA nucleobases forming stable platinum–nitrogen covalent bonds, which lead to irreversible adducts responsible for cisplatin antitumor activity [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of cisplatin with deoxyribonucleic acid (DNA) inside the nucleus causes cell death and apoptosis. Previous studies have found that the interaction occurs between cisplatin and the DNA bases, especially guanine-N(7) but also adenine-N(3) [8]. The interaction of cisplatin with DNA has been studied extensively using X-ray crystallography and NMR spectroscopy in addition to Liquid Chromatography Mass Spectrometry (LCMS) [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Because the main target of the platinum complexes is DNA, understanding the effect of these drugs on DNA conformation is essential [8,15]. After hydrolysis of the chloride leaving group the complex is in a form in which it can interact with DNA [11,16,17].…”
Section: Introductionmentioning
confidence: 99%